2016
DOI: 10.1097/coc.0000000000000091
|View full text |Cite
|
Sign up to set email alerts
|

Asian Versus Non-Asian Outcomes in Nasopharyngeal Carcinoma: A North American Population-based Analysis

Abstract: In this population-based study, Asian ethnicity was associated with improved DSS and OS. Concurrent chemoRT conferred more benefit among non-Asian compared with Asian subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 18 publications
3
16
0
Order By: Relevance
“…Our finding that non‐Hispanic Asians/Pacific Islanders had the highest disease‐specific of any other race/ethnicity has been reported previously but these studies mostly compared them with the White population in the United States . In our study, we compared rates to other minority populations, and the results remained the same as those previously published.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Our finding that non‐Hispanic Asians/Pacific Islanders had the highest disease‐specific of any other race/ethnicity has been reported previously but these studies mostly compared them with the White population in the United States . In our study, we compared rates to other minority populations, and the results remained the same as those previously published.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, we compared rates to other minority populations, and the results remained the same as those previously published. Possible explanation for this favourable prognosis among non‐Hispanic Asians/Pacific Islanders suggested in the literature include younger age at diagnosis, Chinese ethnicity and genetics . Undifferentiated nonkeratinising histology (formerly known as the World Health Organisation (WHO) type III) may also contribute to the favourable prognosis in this race group .…”
Section: Discussionmentioning
confidence: 99%
“…77 The overall incidence of NPC was significantly more common in Asians than in Caucasians. The Asians had a predominance of NK histology (90%), and among Caucasians, NK-NPC was present in 57%.…”
Section: Staging Treatment Prognosis and Risk Of Secondary Malignamentioning
confidence: 99%
“…NPC has also been linked to infection with human papilloma virus (HPV), but co‐infection is common in high‐incidence regions such as Southeast Asia . Analysis of multi‐ethnic patient populations in North America has revealed that Asian patients tend to be diagnosed with keratinising squamous cell carcinoma (type I NPC) at significantly lower rates than do white, black, or Hispanic patients . Among Asian patient populations in high‐incidence regions, the rate of diagnosis of type IIb (non‐keratinising undifferentiated) NPC is frequently greater than 90% .…”
Section: Introductionmentioning
confidence: 99%